Research on the Effect of Brand Spokesperson’s Choice on Consumers’ Purchase Intention——Take “Yang Li Intel Event” as an example - Tai, Yimin (Economics & Management Review, 2022)
In 2021, the event of Yang Li’s endorsement of Intel attracted the attention of the whole network. A discussion was triggered by Yang Li’s controversial remarks, which directly led to the fluctuation of the purchase intention of Intel consumers. With the trend of product homogenization in the market, the brand spokesperson is crucial to the development of the brand. This paper, starting from the hot issue of Yang Li Intel, uses questionnaire investigation and in-depth interview to study the impact of the choice of brand spokesperson on consumers’ purchase intention from the short-term and long-term dimensions. The study found that, in the short term, the more controversial the choice of spokespersons is, the greater the brand awareness is, and the lower the product purchase desire is. In the long run, the more conflicting the choice of spokesmen, the higher the brand awareness, and the higher the desire to buy the brand products when purchasing related products in the later stage. Under the influence of the sleeper effect, consumers’ willingness to buy increased rather than decreased, in which brand awareness and goodwill played a mediating role. These findings provide a reference for brand choice spokesmen, and further expand the research of effect research in the time dimension.